2013
DOI: 10.1007/978-3-642-40246-3_45
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Visual Inspection System for the Classification of the Phases of Ti-6Al-4V Titanium Alloy

Abstract: Abstract. Metallography is the science of studying the physical properties of metal microstructures, by means of microscopes. While traditional approaches involve the direct observation of the acquired images by human experts, Computer Vision techniques may help experts in the analysis of the inspected materials. In this paper we present an automated system to classify the phases of a Titanium alloy, Ti-6Al-4V. Our system has been tested to analyze the final products of a Friction Stir Welding process, to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Ti6Al4V in an α + β alloy exhibited prolonged biocompatibility, high fatigue resistance and toughness, as well as higher tensile strength and density (4.41 g/cm 3 , [ 6 ]) than AlSi10Mg alloy [ 17 , 18 ]. At the same time, its corrosion resistance makes it possible to use in marine and chemical industries and in the biomedical field for orthopedic, cranial and orthodontic implants [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ti6Al4V in an α + β alloy exhibited prolonged biocompatibility, high fatigue resistance and toughness, as well as higher tensile strength and density (4.41 g/cm 3 , [ 6 ]) than AlSi10Mg alloy [ 17 , 18 ]. At the same time, its corrosion resistance makes it possible to use in marine and chemical industries and in the biomedical field for orthopedic, cranial and orthodontic implants [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…At 610 o C a process of crystallization takes place for the 45S5 composition, and another one around 800 o C, these temperatures vary depending on the size particle or thickness of the coating and the heating conditions [31]. Besides, the chosen temperatures were designated in a range were titanium alloy crystal structures remain unchanged [32]. The heating rate should be slow to avoid large temperature gradients and stresses which could result in cracking of the material.…”
Section: Coating Depositionmentioning
confidence: 99%
“…This is due to the high-temperature gradient and the high solidification rate in the melting pool. This microstructure results in rather low elongation (EL) and a low strainhardening rate of as-printed Ti6Al4V samples (Ahmed and Rack, 1998;Ducato et al, 2013;Huang et al, 2016;Barriobero-Vila et al, 2017). It has also been widely reported that there was a high residual stress in as-printed Ti6Al4V (Simonelli et al, 2014;Yadroitsev and Yadroitsava, 2015;Yadroitsava et al, 2015;Parry et al, 2016).…”
Section: Introductionmentioning
confidence: 96%